Too Many Rationales, Not Enough Reason: A Call to Examine the Goals of Including Lay Members on Institutional Review Boards. (2nd January 2016) - Solomon, Stephanie
ABSTRACT: Every major U.S. commission appointed to review Institutional Review Boards (IRBs) as well as numerous reports and scholarly articles have recommended increasing the number of lay (nonscientist and unaffiliated) members on IRBs. Meanwhile, qualitative studies have shown that lay IRB members experience confusion about their roles, including ambiguity whether their roles are different from other members of the board. Without articulating the unique reasons why unaffiliated and nonscientist members are needed, IRBs have little guidance on how to recruit and train these members, and how many should be at the table. By looking back through the history of IRB regulations, policies, and commentaries we can articulate unique contributions these members can make. Only with these contributions in mind can we make arguments for how to best achieve them and make the case that increasing their numbers is necessary.